Designing highly transparent electropolymerized PANI/rGO nanocomposite as a Pt-free electrocatalytic layer in photoelectrochromic device for self-powered green building. (November 2022) - Chiang, Yu-Jou; Chang, Ling-Yu; Cheng, Chao-Yuan; Chang, Ching-Cheng; Yeh, Chia-Lin; Huang, Chen-Jui; Jiang, Shi-Kai; Ho, Kuo-Chuan; Hwang, Bing-Joe; Yeh, Min-Hsin
Abstract: The multifunctional device combining electrochromic and photovoltaic performance is defined as a photoelectrochromic device (PECD), which is designed for self-powered smart window applications. Conventionally, Pt is used as an electrocatalyst to reduce the I3 − in the electrolyte of PECD. However, the optical contrast of PECD with Pt-based counter electrode (CE) is restricted by an intrinsic opaque. In view of this problem, a polyaniline/reduced graphene oxide (PANI/rGO) nanocomposite electrocatalytic layer with highly optical transmittance and good electrocatalytic performance is designed to replace conventional Pt-based CE for further improving the optical performance of the corresponding PECD. Based on the advantages of low cost and promising electrocatalytic activity of PANI, highly transparent and remarkable conductive rGO is introduced to further boost up its electrical conductivity and electrochemical performance. To embed the rGO into the matrix of PANI uniformly, PANI/rGO nanocomposite is deposited on the conductive glass of ITO via electropolymerization. After systematically optimizing the film thickness and composition of PANI/rGO nanocomposite, the PECD with optimized PANI/rGO based CE possesses better optical contrast (ΔT = 26.8%) than that with Pt-based CE (ΔT = 9.4%), which clearly reveals that PANI/rGO nanocomposites with high optical transparency and electrocatalytic ability have the great potential to replace traditional Pt CE in PECDs. Graphical abstract: Image 1 Highlights: High optical transmittance and good electrocatalytic of PANI/rGO electrode is designed for PECD. Conductive rGO is introduced to boost the electrochemical ability of PANI. Quinoid rings of PANI in the nanocomposite became stable by π–π interactions with rGO. PECD with CE of PANI/rGO possesses better optical contrast than that with CE of Pt.